(untitled) (Chittagong University Journal of Biological Sciences, 2025)
Riverbank erosion causes significant loss of agricultural land and homes, profoundly impacting the social, psychological, economic, and environmental well-being of local communities in Bangladesh. This study evaluates the impact of riverbank erosion and communities resilience in Banshkhali Upazila, Bangladesh, using mixed methods approaches like field investigations and focus group discussions (FGDs). The study involves 150 questionnaires and six FGDs to explore socio-economic impacts and adaptation strategies. Findings show severe damage like 20% of homesteads, livestock, and crops being completely destroyed, while 51% of homesteads, 45% of livestock, and 61% of crops are partially damaged. Migration patterns show that 64% of displaced individuals relocated to Chattogram., highlighting the necessity for focused assistance in urban areas. The study highlights the urgent need for integrated management strategies, combining structural and non-structural measures, to strengthen community resilience and reduce the impacts of riverbank erosion. Chittaging Univ. J. B. Sci. Vol. 13 (1&2): 77-85, 2025